Water quality assessment and pollution source analysis in Bukavu urban rivers of the Lake Kivu basin (Eastern Democratic Republic of Congo) - Arthur Mubwebwe Bisimwa; Fabrice Muvundja Amisi; Célestin Maando Bamawa; Bamba Bukengu Muhaya; Alidor Busanga Kankonda (Environmental and Sustainability Indicators, 2022)
The assessment of water quality in Bukavu urban rivers (Kahuwa (KW), Wesha (WS), Tshula (TL), Bwindi (BN), and Nyamuhinga (NG)) was conducted twice a month from 2017 to 2019 at low and high frequencies following standard sampling techniques. Results showed that water temperature (WT), dissolved oxygen (DO), and electrical conductivity (EC) were within WHO standards for surface waters, except pH for some stations on KW and NG rivers, where it was highly alkaline. However, PO43−, NH4+, NO2− and NO3− concentrations increased gradually from upstream to downstream and were very high compared to the WHO standards, which means the river waters were heavily polluted. The highest nutrients concentrations were recorded in the dry season for all rivers, except KW and NG rivers at the midstream and downstream stations. The nutrient average fluxes collected at low-frequency (FLF) and high-frequency (FHF) downstream of each river were 95% correlated. Flux variations regarding PO43−, NH4+, NO2− and NO3− were significant for all rivers except PO43− in the NG river. The number of nutrients exported to Lake Kivu was estimated to average 0.6 t km−2 of PO43−, 2.4 t km−2 of NH4+, 1.0 t km−2 of NO2− and 41.0 t km−2 of NO3− per year. Given the current deterioration status of water quality in Bukavu urban rivers, there is an urgent need to improve liquid and solid waste management strategy in the area, to set up efficient wastewater treatment plants and sewage systems in various catchments to mitigate cumulative pollution of the rivers and the lake.